Hyphenated: A Collaborative Meditation on Research-Creation (Imaginations: Journal of Cross-Cultural Image Studies, 2025)
This article draws on a dialogic form to probe the hyphen at the heart of research-creation, a burgeoning episteme. We, both authors, contend that this hyphen is bound up with solidarity, in the sense of forging communal spirit in the often-depersonalized realm of the academy. We also contend that it’s bound up with intimacy, in the sense of forging proximity between different media and disciplines and between the people practicing them, who are both separate and yet not so apart. In the end, we transcribe an impromptu dance party that took place in a seminar room in the winter of 2024, offering this up as a vision for the models of intimacy (you and me) and space-sharing (us) that research-creation might fruitfully imply.